Electrodynamics of geoenvironment and methods of geoelectrics - V. N. Shuman (Геофизический журнал, 2010)
A brief review of a set of aspects of interaction of electromagnetic waves with geological medium, models of geo-medium and mechanic-electro-magnetic-transformations in it has been done. It is noticed that a real seismo-electro-magneto-generating medium cannot be considered as a linearly-elastic passive continuum - some internal self-similar structure is specific to it which determines its seismic and electromagnetic processes. A conclusion has been made on the close connection of the field of electromagnetic emission structure as well as of micro-seismic vibrations structure registered on the earth's surface with topology of inter-block space and the structure of blocks itself which is formed by the mechanisms of geo-medium self-organization. Some problems of electrodynamics of active media with self-similar structure are considered. Attention is paid to non-adequacy of operating with some effective phenomenological electromagnetic parameters, in particular with refraction index in case of the analysis of emission and propagation processes in the active blocky-hierarchic medium. Existence is noted of the complex of non-linear interaction between both the physical fields and sub-systems of geo-medium, the possibility of appearance of weakly decaying spiral (helicoidal) electromagnetic vibrations (spiral auto-waves). Possibilities of application of electromagnetic component of lithosphere emission aimed at diagnostics of its structure and dynamics are considered making stress on non-classical approaches and methods actual from the viewpoint of geo-electrical applications.